Compreensão da leitura e raciocínio inferencial de um grupo de jovens aprendizes trabalhadores - Santos, Karina Alves dos (2018)
In this research, is used a cognitive approach which objectifies to analyze the profile, in terms of reading, of a young apprentice-workers group, who present a worrying reading comprehension deficit and inferential reasoning. By a reading comprehension activity, it is possible to verify what they understand from the reading and how they use their inferences as reading strategy. 75 young apprentices took part in the research, and three tools were employed for the data collection: a questionnaire, two texts, each one with ten questions and multiple-choice answers, and eight sentences with questions that required inferential reasoning. In the analysis, a qualitative data evaluation was fulfilled, which allowed to verify a low level of young people's interest in reading, as well as to ascertain that many of them present comprehension difficulties and use less inferences in the text comprehension activities. Beyond this, it is possible to identify a low level of reading comprehension, mainly in respect of the inferring ability. Thus, the results suggest the necessity and the importance of schools to offer bigger reading development opportunities, ensuring as the alphabetic system proficiency as the inferential reasoning development, especially in high school